Intensity Modulated High Dose Rate (HDR) Brachytherapy Using Patient Specific 3D Metal Printed Applicators: Proof of Concept - Sohn, James J.; Polizzi, Mitchell; Kang, Sang-Won; Ko, Woo-Hyeong; Cho, Yong-Hyun; Eom, Keun-Yong; Chung, Jin-Beom (Frontiers in Oncology, 2022)
In high-dose-rate (HDR) brachytherapy, an anisotropic dose distribution may be desirable for achieving a higher therapeutic index, particularly when the anatomy imposes challenges. Several methods to deliver intensity-modulated brachytherapy (IMBT) have been proposed in the literature, however practical implementation is lacking due to issues of increased delivery times and complicated delivery mechanisms. This study presents the novel approach of designing a patient-specific inner shape of an applicator with 3D metal printing for IMBT using an inverse plan optimization model. The 3D printed patient-specific HDR applicator has an external shape that resembles the conventional brachytherapy applicator. However, at each dwell position of the HDR source, the shielding walls in the interior are divided into six equiangular sections with varying thicknesses. We developed a mathematical model to simultaneously optimize the shielding thicknesses and dwell times according to the patient’s anatomical information to achieve the best possible target coverage. The model, which is a bi-convex optimization problem, is solved using alternating minimization. Finally, the applicator design parameters were input into 3D modeling software and saved in a 3D printable file. The applicator has been tested with both a digital phantom and a simulated clinical cervical cancer patient. The proposed approach showed substantial improvements in the target coverage over the conventional method. For the phantom case, 99.18% of the target was covered by the prescribed dose using the proposed method, compared to only 58.32% coverage achieved by the conventional method. For the clinical case, the proposed method increased the coverage of the target from 56.21% to 99.92%. In each case, both methods satisfied the treatment constraints for neighboring OARs. The study simulates the concept of the IMBT with inverse planning using the 3D printed applicator design. The non-isotropic dose map can be produced with optimized shielding patterns and tailored to individual patient’s anatomy, to plan a more conformal plan.